Social Capital for Sustainable Salt Farming in Jono Village Tawangharjo District Grobogan Regency - Istikomah, Istikomah; Wijaya, Atika (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
Salt is generally produced in coastal areas using seawater as a raw material. However, this differs from the salt farming at Jono Village, Tawangharjo District, Grobogan Regency, which produces salt from brine wells. Unique and rare, is the nickname for Jono Village, which is geographically located far from the coast. However, the Jono Village salt farming business's sustainability is worrying due to the decreasing number of Jono salt farmers. This article describes the forms of social capital Jono salt farmers utilize to maintain the sustainability of Jono salt farming business. A social group can use social capital to overcome their problems. This research uses a qualitative approach. Data collection was carried out using observation, interviews, and documentation techniques. Social capital that develops in the Jono salt production center includes klakah as an adhesive for the relationship between Jono salt farmers and the cooperative relationships built by Jono salt farmers with middlemen and capital providers. Klakah is a social capital medium facilitating social interaction and internalizing collective values. Relationships with middlemen are established in the Jono salt distribution system. Capital providers consist of banks that provide business credit, village cooperatives, and fellow Jono salt farmers who offer financial assistance in a loan scheme.  Bonding social capital is reflected in the togetherness and cooperative attitude of Jono salt farmers. Meanwhile, bridging social capital can be found in the networks built by Jono salt farmers, both among themselves and with outside parties such as middlemen and capital providers. Social capital is useful in supporting the sustainability of the Jono salt farming business.